Absolute pharmacokinetics of heparin in primates - Song, Yuefan; Kouta, Ahmed; Cera, Lee M.; Xia, Ke; Zhang, Fuming; Krämer, Roland; Fareed, Jawed; Linhardt, Robert J.; Jeske, Walter (Carbohydrate polymers, 2023)
Heparin is a commonly used anticoagulant drug, derived from the tissues of animals including pigs, cows, and sheep. Measuring heparin concentration in plasma is challenging due to its complex molecular structure. Existing methods rely on measuring heparin's anticoagulant activity, which provides pharmacodynamic (PD) data but not pharmacokinetic (PK) data, measuring concentration over time. To overcome this limitation, we used liquid chromatography-mass spectrometry (LC-MS) and the multiple reaction monitoring (MRM) method to directly measure heparin's concentration in non-human primates after administering porcine, bovine, and ovine heparin. A protocol was developed to enable an MRM method for application to small plasma volumes without purification. The PK data obtained from LC-MS are then compared with the data obtained using the Heparin Red assay and the PD data determined using biochemical clinical assays. Results showed that LC-MS and Heparin Red assay measurements closely correlated with unfractionated heparin's biological activities, supporting the use of mass spectra and dye-binding assays to determine heparin levels in plasma. This study builds a way for the measurement of heparin concentration in plasma, which could lead to an improved understanding of heparin's metabolism and dosing safety.